2018
DOI: 10.3727/096504018x15223171140640
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy analysis of DEB-TACE treatment in elderly patients with hepatocellular carcinoma: a comparative cohort study

Abstract: The aim of this study was to explore the difference of liver function change, safety profiles and efficacy of drug-eluting bead transarterial chemoembolization (DEBTACE) therapy between elderly and middle-aged hepatocellular carcinoma (HCC) patients. 91 HCC patients were enrolled in this prospective cohort study. They were treated by DEB-TACE therapy and divided into elderly group (age >= 65 years, n=30) and middle-aged group (age < 65 years, n=61), liver function, safety profiles and treatment response were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… 31 Furthermore, In elderly individuals diagnosed with HCC, drug-eluting bead transarterial chemoembolization (DEB-TACE) is well tolerated. 32 However, further studies have yet to explore how different age groups affect the outcome of PA-TACE in HBV-HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Furthermore, In elderly individuals diagnosed with HCC, drug-eluting bead transarterial chemoembolization (DEB-TACE) is well tolerated. 32 However, further studies have yet to explore how different age groups affect the outcome of PA-TACE in HBV-HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that TACE reaches satisfactory efficacy and is well tolerated in elderly patients, including those above 85 years old [ 114 , 115 ]. Recent studies have described that drug-eluting bead-TACE therapy was safe and effective in elderly patients either with HCC [ 116 ] or iCCA [ 117 ].…”
Section: Palliative Treatmentsmentioning
confidence: 99%
“…TACE is considered one of the most effective and safe treatment for advanced liver cancer (11). It is generally assumed to play a considerable role in liver solid tumors, but it has also been reported to have the potential to cause significant damage to liver function (12). There are three reasons that liver injury after TACE are common: the history of concomitant cirrhosis, chemotherapeutic drugs, and the process of ischemia-reperfusion in the liver (13).…”
Section: Introductionmentioning
confidence: 99%